Proxy evidence for state-dependence of climate sensitivity in the Eocene greenhouse - E. Anagnostou (Nature Portfolio, 2020)
The relationship between atmospheric CO2 and climate during the Eocene greenhouse remains uncertain. Here authors show that Eocene CO2 and climate sensitivity was high during the warmest intervals and declined as global climate cooled, with implications for the Earth’s future warming climate.